Polymer Brushes on Hexagonal Boron Nitride - Sheng, Wenbo; Amin, Ihsan; Neumann, Christof; Dong, Renhao; Zhang, Tao; Wegener, Erik; Chen, Wei-Liang; Foerster, Paul; Hai Quang Tray; Loeffler, Markus; Winter, Andreas; Rodriguez, Raul D.; et al. (Small, 2019)
Direct covalent functionalization of large-area single-layer hexagonal boron nitride (hBN) with various polymer brushes under mild conditions is presented. The photopolymerization of vinyl monomers results in the formation of thick and homogeneous (micropatterned, gradient) polymer brushes covalently bound to hBN. The brush layer mechanically and chemically stabilizes the material and allows facile handling as well as long-term use in water splitting hydrogen evolution reactions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 2D materials; hexagonal boron nitride; hydrogen evolution; patterning; polymer brushes